Afrotempos:: creation and displacements in Mesa Farta, by the Pretagô group (Porto Alegre, Brazil) - Pirajira Conceição, Thiago (Revista Brasileira de Estudos da Presença, 2024)
This article, which is part of a doctoral research, reflects on some cosmogonic aspects of Exu, a Yoruban orisha, and his relations with the spectacle Mesa Farta (‘Plentiful Table’), by the theater group Pretagô (Porto Alegre-Brazil). The mythic-philosophical foundations that constitute knowledge of African origins are discussed; scenic strategies developed in the process of creation, that organize a way of thinking about scenic practice itself, based on assumptions distanced from Eurocentric theatrical and performative notions, are identified. It appears that the notion of afrotempo (‘Afro-time’), conceived as a Black strategy for relating to the creation process managed by the group’s artists, enables new approaches to doing and inscribing Black ethics and philosophy in the field of performing arts.